Analysis of clinical and genetic features in a pediatric patient with Kartagener syndrome caused by compound heterozygous mutations in the DNAH5 gene: a case study and literature review - Zhang, Jingli; Gao, Longfei; Xing, Yu; Wu, HuiFang; Liu, Xiaojuan; Zhang, Yingqian (Frontiers in Medicine, 2025)
Kartagener syndrome (KS), a subtype of primary ciliary dyskinesia (PCD), is a rare genetic disorder characterized by situs inversus, chronic sinusitis, bronchiectasis, recurrent respiratory infections, and impaired ciliary function. It is diagnosed through physical examination, imaging techniques such as computed tomography (CT), nasal nitric oxide measurement, genetic testing, and pulmonary function tests. We present a case study of a 15-year-and-11-month-old male patient with KS complicated by sinusitis, secretory otitis media, and bronchiectasis. The patient exhibited situs inversus totalis, affecting the lungs, heart, and abdominal organs. Treatment included antibiotics for infection, mucolytics, and pulmonary rehabilitation. Postural drainage and bronchoscopy were performed for lung lavage. Following treatment, the patient’s respiratory symptoms improved, and lung function tests showed improvement. A literature review identified a high prevalence of lung and heart transpositions in Chinese patients with PCD, while abdominal organ transposition was less commonly reported. Genetic analysis revealed compound heterozygous mutations in the DNAH5 gene, specifically c.12279 + 1 G > A (exon 71, NM_001369) and c.9457 C > T (exon 56, NM_001369), including the newly discovered variant c.9457 C > T (exon 56, NM_001369). This novel mutation expands the genetic landscape associated with KS, providing further insights into the underlying genetic basis of the condition. The study emphasizes the clinical features, the limited reporting of abdominal organ transposition, the genetic basis, and the treatment of KS, thereby contributing to the understanding and management of this condition.